Assessment of medication adherence and treatment satisfaction in Japanese patients with psoriasis of various severities. Issue 6 (21st January 2018) - Ichiyama, Susumu; Ito, Michiko; Funasaka, Yoko; Abe, Masatoshi; Nishida, Emi; Muramatsu, Shinnosuke; Nishihara, Haruna; Kato, Hiroshi; Morita, Akimichi; Imafuku, Shinichi; Saeki, Hidehisa
Abstract: Psoriasis is a chronic, relapsing, inflammatory keratotic skin disease. To elucidate the medication adherence and treatment satisfaction, we performed a questionnaire survey using the eight‐item Morisky Medication Adherence Scale (MMAS‐8) and nine‐item Treatment Satisfaction Questionnaire for Medication (TSQM‐9) of 163 psoriatic patients who regularly visited hospitals or clinics. To assess the relationship between the MMAS‐8/TSQM‐9 outcomes and severity of psoriasis, two different clinical severity indices were used: the Psoriasis Area and the Severity Index (PASI) for disease severity and the Psoriasis Disability Index (PDI) for quality of life (QOL) impairment. The MMAS‐8 score for oral medication was significantly higher than that for topical medication. The oral and topical MMAS‐8 scores were significantly correlated with the PDI score, but not with the PASI score, indicating that QOL impairment lowered treatment motivation. All of the TSQM‐9 domain scores (effectiveness, convenience and global satisfaction) were significantly correlated with both the PASI and PDI scores, suggesting that patients whose skin and QOL conditions were under good control had high satisfaction with treatment. Patients treated with biologics had higher satisfaction than those treated with non‐biologics.